How do I... move out of home? - Brice K. (Moscow State University of Psychology and Education, 2017)
One of the most important steps in the life of an adult person is moving out of family. This can happen due to a change of place of residence to a supported housing or to accommodation at an educational institution. An experienced professional lists the most important things that should be considered by people with autism spec¬trum disorders who are getting ready to leave their homes. Translated from English by T.V. Khapkova, N.A. Voskoboynikova